Leopold Blaustein’s Critique of Phenomenology - Gilicka, Magdalena (Folia Philosophica, 2017)
The present paper presents Blaustein’s critical remarks on the selected assumptions of Husserl’s phenomenological method. The analysis concerns the socalled pretranscendental phenomenology. First, I present the critique of the concept of impressons. Then, I analyze remarks upon aspects pertaining to the concept of materiality and quality of act.